Estudo fitoquímico do óleo essencial dos frutos da aroeira (Schinus terebinthifolius Raddi) e sua eficácia no combate ao dengue - Cole, Eduardo Roberto (2008)
Dengue is considered the most important of the human arbovirosis, constituting nowadays one of the main Public Health problems in the world. The disease is caused by a virus of the genus Flavivirus with four different serotypes, transmitted by mosquitoes of the genus Aedes, and Aedes aegypti its main vector. The control of the vector by synthetic insecticides has been the main procedure adopted in combating the disease, since there are no effective vaccines against the different virus serotypes. The insecticides, although effective, present serious problems related to its use, among which can be highlighted environmental damage, toxicity for human use, and the risk of the selection of resistant larvae and adults. The search for natural and less aggressive insecticide methodologies has considerably grown in the last years, with the use of plant extracts and natural substances. Studies reveal that plant essential oils have many potential biological activities against insects. Schinus terebinthifolius Raddi (Brazilian peppertree) species, well known for its ornamental properties and its use as food condiment, has also been the object of studies of biological activity. In order to provide more information about the chemical identity of the essential oil of the Schinus terebinthifolius fruits and contribute on the discovery of new products to combat dengue, this study aimed to characterize chemically and physical-chemically the essential oil, and also to evaluate its larvicidal , insecticide and repellent activities related to the Aedes aegypti.The results yield of the process of extraction by hydrodistillation (6,54 ± 1,56%) did not present a significant difference between the repetitions. The specific density values (0,9097 ± 0,0200 g/cm3 ), and index of refraction (1,4750 ± 0,0001) of the essential oil showed up close to the available data in the literature, a fact not observed on the specific rotation value (+26,41 ± 0,0200). Thin-Layer Chromatography (TLC) and Gas Chromatography (GC) showed the same chromatographic profile for the samples obtained. The analysis by Gas Chromatography coupled to the Mass Spectrometry (GC/MS) detected 28 volatile substances. Among these, 17 were identified (91,15% of the total identified), among what 12 are monoterpenes and 5 are sesquiterpenes. The predominant chemical species, all monoterpenics were: d-3-carene (30,37%), limonene (17,44%), a-phellandrene (12,60%), a-pinene (12,59%), myrcene (5,82%), and o-cymene (3,46%). The larvicidal, insecticide and repellent activities of the essential oil were highlighted against the Aedes aegypti, being the concentrations 169,20 µg/mL; 50,00 µL and 2,39% (w/w), the most effective, respectively, in each of the tests made. The LC50 obtained was 117,34 µg/mL for the larvicidal test, and 28,80 µL for the insecticide testing.